2020
DOI: 10.1029/2019ms001698
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Aggregation of Convection in Spatially Varying Sea Surface Temperatures

Abstract: The phenomenon of self-aggregation of convection was first identified in convection-permitting simulations of radiative convective equilibrium, characterized by homogeneous boundary conditions and in the absence of planetary rotation. In this study, we expose self-aggregation of convection to more complex, nonhomogeneous boundary conditions and investigate its interaction with convective aggregation, as forced by large-scale variations in sea surface temperatures (SSTs). We do this by conducting radiative conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Worth to mention that all the studies mentioned so far used fixed homogeneous surface temperature. Using a nonhomogeneous SST (constant in time but inhomogeneous in space) or an interactive SST (evolving in time) can also change the occurrence of self‐aggregation and the dominating feedback (Hohenegger & Stevens, 2016; Liu & Moncrieff, 2008; Müller & Hohenegger, 2020; Shamekh et al, 2019; Tompkins, 2001). Introducing an SST anomaly can dictate the preferred location of convection (Tompkins, 2001) and thus impact the self‐aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Worth to mention that all the studies mentioned so far used fixed homogeneous surface temperature. Using a nonhomogeneous SST (constant in time but inhomogeneous in space) or an interactive SST (evolving in time) can also change the occurrence of self‐aggregation and the dominating feedback (Hohenegger & Stevens, 2016; Liu & Moncrieff, 2008; Müller & Hohenegger, 2020; Shamekh et al, 2019; Tompkins, 2001). Introducing an SST anomaly can dictate the preferred location of convection (Tompkins, 2001) and thus impact the self‐aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Another improvement of the model will be to take into account ocean circulation. Del Genio et al ( 2019) showed the impact of such circulation on the SST and the clouds self-aggregation (Müller and Hohenegger, 2020) and how SST anomalies can favor the aggregation of convection (Shamekh et al, 2020). The oceanic circulation is also believed to have a significant impact on the atmospheric circulation, with a planetary heat transport dominated by the ocean at moderate incident stellar fluxes and by the atmosphere near the inner edge of the habitable zone Yang et al (2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we have quantified organization in idealized simulations and reanalysis of different geometries to show the versatility of the moist margin's approach. However, this limits our ability to meaningfully compare idealized simulations to observations, as, for example, idealized simulations with weak rotation and meridional surface temperature gradients would be better analogs to the Atlantic ITCZ (e.g., Müller & Hohenegger, 2020).…”
Section: Discussionmentioning
confidence: 99%